Cross-Disease Innate Gene Signature: Emerging Diversity and Abundance in RA Comparing to SLE and SSc. (16th July 2019) - Petrackova, Anna; Horak, Pavel; Radvansky, Martin; Skacelova, Martina; Fillerova, Regina; Kudelka, Milos; Smrzova, Andrea; Mrazek, Frantisek; Kriegova, Eva
Abstract : Overactivation of the innate immune system together with the impaired downstream pathway of type I interferon-responding genes is a hallmark of rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and systemic sclerosis (SSc). To date, limited data on the cross-disease innate gene signature exists among those diseases. We compared therefore an innate gene signature of Toll-like receptors (TLRs), seven key members of the interleukin (IL)1/IL1R family, and CXCL8/IL8 in peripheral blood mononuclear cells from well-defined patients with active stages of RA (n = 36, DAS 28 ≥ 3.2 ), SLE (n = 28, SLEDAI > 6 ), and SSc (n = 22, revised   EUSTAR   index > 2.25 ). Emerging diversity and abundance of the innate signature in RA patients were detected: RA was characterized by the upregulation of TLR3, TLR5, IL1RAP/IL1R3, IL18R1, and SIGIRR/IL1R8 when compared to SSc (P corr < 0.02 ) and of TLR2, TLR5, and SIGIRR/IL1R8 when compared to SLE (P corr < 0.02 ). Applying the association rule analysis, six rules (combinations and expression of genes describing disease) were identified for RA (most frequently included high TLR3 and/or IL1RAP/IL1R3 ) and three rules for SLE (low IL1RN and IL18R1 ) and SSc (low TLR5 and IL18R1 ). This first cross-disease study identified emerging heterogeneity in the innate signature of RA patients with many upregulated innate genes compared to that of SLE and SSc.